Efektivitas Model Pembelajaran Discovery Ditinjau dari Kemampuan Komunikasi Matematis Siswa - Sabati, Mila; Gunowibowo, Pentatito; Widyastuti, Widyastuti (FKIP Universitas Lampung, 2018)
The Effectiveness of Discovery Learning Model in Terms of Students’ Mathematical Communication Skills. This quasi experimental research aimed to examine the effectiveness of discovery learning model in terms of students’ mathematical communication skills. The population of this research was all students of grade VII of SMP Negeri 26 Bandarlampung in even semester in academic year 2018/2019 as many as 233 students, that were distributed into eight classes. By using purposive sampling technique, two classes were taken as the sample that were VII B class as many as 30 students and VII D class as many as 29 students. This research used the pretest-posttest control group design and the data collecting technique was test. The data obtained from this research was the score of students’ mathematical communication skills. Based on the result of -test and proportion test using 5% of significance level, it was concluded that discovery learning model was not effective in terms of students’ mathematical communication skills. However, the mathematical communication skills of students who following discovery learning was higher than mathematical communication skills of students who following conventional learning.Keywords: discovery learning, effectiveness, mathematical communication skills DOI: http://dx.doi.org/10.23960/jpmipa/v19i2.pp87-98